The Institutional Economics of Water : A Cross-Country Analysis of Institutions and Performance - Saleth, R. Maria, 1955- 1955- (The World Bank, 2004)
The Institutional Economics of Water evaluates water institutional reform and water sector performance from an institutional economics and political economy perspective. Against an exhaustive review of the theoretical and empirical literature on institution and performance both in general and in water sector contexts, the title develops an alternative methodology built on: 'institutional ecology' principle, 'institutional decomposition and analysis' framework, and 'subjective theory' of institutional change. Empirical application of this methodology with information collected from 127 water experts from 43 countries/regions and a cross-country review of recent water sector reforms within an institutional transaction cost framework enables the book to conclude with significant implications for both theory and policy in the realm of water sector reform in particular and institutional reforms in general. 'We are both impressed by the book. It will merit prominent publication as a far-reaching application of innovative methodologies to an important, and well explained, worldwide policy problem.' - Randall Calvert, Washington University, St. Louis, US and Thrainn Eggertsson, University of Iceland '[The] literature review . . . is one of the best and most comprehensive that I have seen.' - Daniel W. Bromley, University of Wisconsin, US